Upaya Preventif Lansia pada Penyakit Diabetes Melitus - Uchira Uchira; Jamila Kasim; Rasdin Rasdin (Lembaga Pengembangan Kinerja Dosen, 2024)
Elderly people have a high risk of suffering from degenerative diseases, one of which is metabolic disorders. This is more widely recognized by the elderly when they are already in severe condition and with complications so that it has an impact on various aspects including increasing morbidity and mortality rates, as well as decreasing quality of life of the elderly and decreasing ability of the elderly to carry out daily activities. Metabolic disorders are caused by increased blood glucose levels in the body known as Diabetes Mellitus (DM) which is one of the health problems of the ten diseases that cause death and disability globally. The implementation of community service activities for Preventive Efforts for the Elderly in Diabetes Mellitus through several stages, namely the survey and field observation stages and counseling for Preventive Efforts for the Elderly in Diabetes Mellitus counseling is carried out for approximately 90 minutes, as well as evaluations in the form of pre-tests and post-tests. The provision of education was carried out on Wednesday, November 14, 2024 at the Antara Health Center, the number of participants was 32 people. Based on the results of the knowledge of the elderly before and after the counseling for Preventive Efforts for the Elderly in Diabetes Mellitus, it was found that 15 elderly people had sufficient knowledge and 17 elderly people had insufficient knowledge. After conducting counseling on Preventive Efforts for the Elderly in Diabetes Mellitus, the results obtained were a sufficient increase of 30 and less than 2 elderly. This means that community service on Preventive Efforts for the Elderly in Diabetes Mellitus is very effective in the elderly in order to prevent an increase in glucose levels. Counseling on preventive efforts for the elderly in diabetes regarding these degenerative diseases is very necessary so that the elderly maintain their health better. The elderly are expected to be able to understand about efforts to prevent and treat degenerative diseases in the elderly with diabetes. Hopefully this community service can be a reference for researchers and further community service, as well as the community.